Navigating the Crossroads of Cell Therapy and Natural Heart Regeneration - Elde, Stefan; Wang, Hanjay; Woo, Y. Joseph (Frontiers in Cell and Developmental Biology, 2021)
Cardiovascular disease remains the leading cause of death worldwide despite significant advances in our understanding of the disease and its treatment. Consequently, the therapeutic potential of cell therapy and induction of natural myocardial regeneration have stimulated a recent surge of research and clinical trials aimed at addressing this challenge. Recent developments in the field have shed new light on the intricate relationship between inflammation and natural regeneration, an intersection an that warrants further investigation.